Tailored ASD destabilization - Balancing shelf life stability and dissolution performance with hydroxypropyl cellulose - Christian Luebbert; Edmont Stoyanov (Elsevier, 2023)
Amorphous solid dispersion (ASD) formulations are preferred enabling formulations for poorly water soluble active pharmaceutical ingredients (API) as they reliably enhance the dissolution behavior and solubility. Balancing a high stability against unwanted transformations such as crystallization and amorphous phase separation during storage on the one hand and optimizing the dissolution behavior of the formulation (high supersaturation and maintenance for long time) on the other hand are essential during formulation development. This study assessed the potential of ternary ASDs (one API and two polymers) containing the polymers hydroxypropyl cellulose together with poly(vinylpyrrolidone-co-vinyl acetate) (PVP VA64) or hydroxypropyl cellulose acetate succinate to stabilize the amorphously embedded APIs fenofibrate and simvastatin during storage and to enhance the dissolution performance. Thermodynamic predictions using the PC-SAFT model revealed for each combination of polymers the optimal polymer ratio, maximum API load that is thermodynamically stable as well as miscibility of the two polymers. The stability predictions were validated by three months enduring stability tests, followed by a characterization of the dissolution behavior. The thermodynamically most stable ASDs were found to be the ASDs with deteriorated dissolution performance. Within the investigated polymer combinations, physical stability and dissolution performance opposed each other.